Industrial Applications of Superhydrophobic Coatings: Challenges and Prospects - Erbil, Husnu Yildirim (My University, 2020)
The use of the superhydrophobic coatings and materials in industry is not satisfactory after the intensive activity inresearch laboratories in the last two decades. We discussed the reasons for this adverse situation under several topicsin this review article. The most important issues are the insufficient mechanical resistance and inevitable contaminationof the SH surfaces under outdoor conditions, resulting in short useful life-time. The fabrication of a SH surface requires arough structure with tiny textures on it and this frail framework has a poor mechanical resistance. The topics of superfluousproduction of small scale and expensive SH surfaces, the difficulty to obtain transparent and also self-healing SH surfaces,the inefficient anti-icing applications of the SH coatings are also discussed.
Keywords: Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Kaplamalar ve Filmler; Mühendislik; Kimya